A LEGAL FRAMEWORK ANALYSIS OF LAND TENURE CONFLICTS BETWEEN LOCAL COMMUNITIES AND PALM OIL CONCESSIONS IN WEST KALIMANTAN - Loso Judijanto; Dina Ahmed; Mariam Hassan (Journal of Selvicoltura Asean, 2025)
The rapid expansion of oil palm plantations in West Kalimantan, Indonesia, has precipitated a surge in protracted and often volatile land tenure conflicts between concession holders and local communities. These disputes are frequently rooted in a complex and fragmented legal landscape, where competing claims over land ownership and use rights collide. This study aimed to critically analyze the existing legal framework governing land tenure and concession licensing in West Kalimantan to identify the specific legal ambiguities, contradictions, and gaps that contribute to and perpetuate these conflicts. A qualitative legal framework analysis was conducted. The research systematically reviewed and analyzed a hierarchy of legal instruments, including Indonesia’s Basic Agrarian Law, Forestry Law, and investment regulations, alongside provincial land use policies. This was triangulated with an analysis of customary law (hukum adat) and documentation from 25 land conflict case studies. The analysis reveals a state of legal pluralism fraught with conflict. The primary cause of disputes is the state’s non-recognition of customary land rights (tanah ulayat) within the concession licensing (HGU) process. Significant procedural flaws, including a lack of free, prior, and informed consent (FPIC) and inadequate compensation mechanisms, were found to consistently disenfranchise local communities, rendering their claims legally invisible. Endemic land tenure conflicts in West Kalimantan are a direct consequence of a dysfunctional legal framework that fails to recognize and protect community rights. Resolving these disputes necessitates fundamental legal reform, including the formal legal recognition of customary land tenure and the mandatory integration of robust FPIC principles into all stages of the concession licensing process.